2021
DOI: 10.1063/5.0042478
|View full text |Cite
|
Sign up to set email alerts
|

Controlled oxidation and surface modification increase heating capacity of magnetic iron oxide nanoparticles

Abstract: Magnetic iron oxide nanoparticles (MIONs) can generate heat under an alternating magnetic field, enabling a wide range of applications from water treatment to cancer hyperthermia therapy. For most magnetic heating applications, it is crucial to generate a high level of heat with a low dose of MIONs. Current methods to increase the specific absorption rate (SAR) of MIONs include increasing their size and doping iron oxide nanocrystals with other metal elements. Here, we demonstrate that controlled oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Ferrimagnetic glass-ceramic have been successfully used as thermo-seeds for a hyperthermic treatment of carcinoma cells in Sprague-Dawley rats [589], whereas magnetite cationic liposomes where used to generate hyperthermia on local tumors and lung metastases in a mouse model of osteosarcoma [590]. Spinel ferrite nanoparticles were successfully synthesized and used for MHT [591], whereas MIONs (such as crack-free ferrimagnetic maghemite, γ-Fe 2 O 3 ) may be useful for the in situ hyperthermic treatment of cancer [592][593][594][595]. SPIONs have been increasingly studied for their excellent MHT applications [596,597], whereas lanthanum-strontium manganite particles that were embellished with gold nanoparticles were found to be suitable for the treatment of deeper tumors [598].…”
Section: Magnetic Hyperthermia Ad Cancer Treatmentmentioning
confidence: 99%
“…Ferrimagnetic glass-ceramic have been successfully used as thermo-seeds for a hyperthermic treatment of carcinoma cells in Sprague-Dawley rats [589], whereas magnetite cationic liposomes where used to generate hyperthermia on local tumors and lung metastases in a mouse model of osteosarcoma [590]. Spinel ferrite nanoparticles were successfully synthesized and used for MHT [591], whereas MIONs (such as crack-free ferrimagnetic maghemite, γ-Fe 2 O 3 ) may be useful for the in situ hyperthermic treatment of cancer [592][593][594][595]. SPIONs have been increasingly studied for their excellent MHT applications [596,597], whereas lanthanum-strontium manganite particles that were embellished with gold nanoparticles were found to be suitable for the treatment of deeper tumors [598].…”
Section: Magnetic Hyperthermia Ad Cancer Treatmentmentioning
confidence: 99%
“…Magnetic anisotropy is also a significant parameter that influences the hyperthermic efficiency of MNPs [ 49 ]. With the determined T B value, the anisotropy constant K A of MNPs with no magnetic interactions can be calculated by [ 50 ]. where t 0 is the timescale of the measurement (100 s), τ 0 is the microscopic jump time (10 −9 s), k B is the Boltzmann constant, and V is the volume of MNPs, which can be estimated using the average particle diameter determined via TEM measurements (spherical shape approximation).…”
Section: Resultsmentioning
confidence: 99%
“…At room temperature, magnetite exhibits a spin-polarized conductivity due to the rapid hopping of the additional electron every two Oh sites [11] (see section 2). However, as a result of electronic transitions due to overlapping Fe-3d orbitals [120,121], there is a weak electron localization into a polaron responsible for an intervalence charge transfer band in the near infrared radiation (NIR) region (0.6-1 eV), which has been exploited by some authors to monitor the conversion between magnetite and maghemite [25,120,122]. For example, by following the absorbance of a NP suspension, Jung and Schimpf [122] showed that a colloid of maghemite NPs can be reduced to magnetite by using ethanol as a sacrificial reductant during UV irradiation (figure 3(b)).…”
Section: Spectrophotometrymentioning
confidence: 99%
“…The magnetite lattice can accommodate a full range of stoichiometries (Fe 3−x O 4 ) between stoichiometric magnetite (x = 0) and maghemite (x = 0.33) and it has been demonstrated that the physicochemical response behind most applications depends on the Fe 2+ concentration. For example, the contaminant reduction rates can change several orders of magnitude due to variations in the amount of Fe 2+ [24], whereas the magnetic properties and the heating efficiency of the NPs are strongly modulated by their oxidation degree [25]. While many applications rely on a precise control of the iron oxide stoichiometry, it is known that magnetite NPs transform into maghemite in a topotactic (i.e.…”
Section: Introductionmentioning
confidence: 99%